Long-Term Success of Dental Implants in Atrophic Maxillae: A 3-Year Case Series Using Hydroxyapatite and L-PRF - Marco Andre Lomba Alves; Jakson Both; Carlos Fernando Mourão; Bruna Ghiraldini; Fabio Bezerra; Jose Mauro Granjeiro; Suelen Cristina Sartoretto; Monica Diuana Calasans-Maia (Bioengineering)
Dental implants are essential for the prosthetic rehabilitation of edentulous patients, requiring adequate bone volume and density for osseointegration and load support. The posterior region of the maxilla, commonly deficient in bone quality and quantity, represents a clinical challenge. This case series reports an analysis involving 69 dental implants in the atrophic maxilla of nine patients. The procedures adopted combined alloplastic hydroxyapatite grafting and leukocyte platelet-rich fibrin (L-PRF) applied to the alveolar ridge and maxillary sinus lift. With an average follow up of three years after the installation of the prostheses, an implant success rate of 98.5% was observed, showing integration and functional stability. The strategy of combining hydroxyapatite with L-PRF proved to be effective in increasing bone volume and promoting osseointegration. These findings indicate that the technique and biomaterials are viable for rehabilitating atrophic maxillae in the posterior region, offering long-lasting clinical results and a high success rate.